Impedance spectroscopy: Over 35 years of electrochemical sensor optimization - Pejcic, Bobby; De Marco, Roland (Pergamon-Elsevier Science Ltd, 2006)
There is considerable interest in the development of electroanalytical sensors (i.e., potentiometric, amperometric, electrochemical biosensors) for the detection of a wide range of analytes. The success of many of these sensors is governed by the condition and stability of the membrane/electrode surface. In fact, the response mechanism is dictated primarily by the surface structure and a considerable amount of work has been undertaken to characterize the interfacial region. Consequently, electrochemical impedance spectroscopy (EIS) has played a pivotal role in the characterization of many types of sensors. EIS has been used to provide information on various fundamental processes (i.e., adsorption/film formation, rate of charge transfer, ion exchange, diffusion, etc.) that occur at the electrode electrolyte interface. Understanding and manipulating these interfacial processes has assisted in the development of membranes/electrodes with new and improved response characteristics. This paper reviews some of the work that has been undertaken using EIS over the past 35 years. More importantly, it evaluates the power of EIS in characterizing a wide range of electrochemical sensor systems.